CELEBRITY ENDORSEMENT ON MILLENNIAL CUSTOMERS’ PURCHASING BEHAVIOUR - Mohd Amirul Atan; Fadhilah Zainal Abidin; Farith Azizi Mohayyaddin Abdul Kader; Natthaphon Santhi; Kannikar Kantamas; Mohd Isham Abidin (International Journal of Accounting, Finance and Business, 2021)
The study reviews relevant literatures in relation to the phenomenon of celebrity endorsement towards millennial customers’ purchasing behaviour. Literatures based on the variables of endorser’s gender, credibility, attractiveness and type) were reviewed in obtaining the overviews of the phenomenon based on past studies. In addition, related literatures on customer purchasing behaviour were also reviewed. This study also includes an overview of celebrity endorsement from the perspective of Thailand’s purchasing behaviour context. Based on the reviews made, some suggestions and recommendations related to the phenomenon are made as a guide for individu